Longitudinal proteomic analysis of pathophysiology in plasma and bronchoalveolar lavage fluid of patients with ARDS - Yumi Mitsuyama; Hisatake Matsumoto; Fuminori Sugihara; Satoshi Fujimi; Hiroshi Ogura; Jun Oda (Journal of Intensive Care)
Abstract Background Acute respiratory distress syndrome (ARDS) remains a significant clinical challenge, and its pathogenesis is not fully understood. Proteomic analyses of plasma and bronchoalveolar lavage fluid (BALF) in patients with ARDS have been performed to uncover diagnostic and prognostic markers, although previous studies have not adequately focused on longitudinal comparison of biomarkers. This study aimed to elucidate the proteomic profiles of patients with ARDS in the acute and subacute phases to better understand the pathophysiological progression of ARDS. Methods This was a single-center, prospective, observational study of adult patients with ARDS in whom plasma and BALF samples were collected in the acute and subacute phases of ARDS and comprehensive proteins were identified and analyzed by mass spectrometry. Results Plasma and BALF were collected from 21 ARDS patients and plasma from 24 healthy donors, from which 694 plasma proteins and 2017 BALF proteins were analyzed. Processes related to coagulation and complement commonly activated in plasma and BALF were more pronounced in the acute phase than in the subacute phase. In BALF in the acute phase, pathways related to humoral and immune responses were activated, whereas processes related to chaperones and protein folding were suppressed. IPA analysis showed that B cell receptor signaling was most activated, whereas heat shock protein 90 (HSP90) chaperone cycle, protein folding, and other pathways associated with cellular stress responses and proper protein processing were suppressed. The most activated upstream regulator was interferon gamma (IFN-γ) and the most suppressed was notch receptor 1 (NOTCH1). Conclusions The proteomics of plasma and BALF from patients with ARDS were compared in both the acute and subacute phases. In BALF in the acute phase, humoral immunity, mainly B-cell receptor signaling, was activated, whereas the HSP90 cycle and protein folding mechanisms were inactivated.